2018
DOI: 10.1021/jacs.8b08030
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Construction of Hierarchical Superstructures Using Shape-Persistent Organic Cages: Porphyrin Box-Based Metallosupramolecular Assemblies

Abstract: We report a new approach to building hierarchical superstructures using a shape-persistent porous organic cage, which acts as a premade secondary building unit, and coordination chemistry. To illustrate the principle, a zinc-metalated porphyrin box (Zn-PB), a corner-truncated cubic porous cage, was connected by suitable dipyridyl terminated bridging ligands to construct PB-based hierarchical superstructures (PSSs). The PSSs were stabilized not only by the coordination bonds between Zn ions and bipyridyl-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 44 publications
1
57
0
1
Order By: Relevance
“…MALDI‐MS and UV/Vis show complete metalation for each catalyst (Figures S3–S4, S6–S10). The porous nature of Co‐PB‐1(6) was confirmed with N 2 sorption analysis giving a Brunauer‐Emmett‐Teller surface area of 562 m 2 g −1 (Figure S15), which is in agreement with our previous report on Zn‐PB‐1(6) . In contrast, N 2 sorption studies showed Co‐rPB‐1(6) to be relatively non‐porous with a surface area of 23 m 2 g −1 .…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…MALDI‐MS and UV/Vis show complete metalation for each catalyst (Figures S3–S4, S6–S10). The porous nature of Co‐PB‐1(6) was confirmed with N 2 sorption analysis giving a Brunauer‐Emmett‐Teller surface area of 562 m 2 g −1 (Figure S15), which is in agreement with our previous report on Zn‐PB‐1(6) . In contrast, N 2 sorption studies showed Co‐rPB‐1(6) to be relatively non‐porous with a surface area of 23 m 2 g −1 .…”
Section: Methodssupporting
confidence: 89%
“…To synthesize the supramolecular catalysts, we first prepared the free‐base porphyrin box, PB‐1(6), through condensation of six tetraformylphenyl porphyrins with eight tripodal triamines bearing hexyloxy solubilizing groups . Treatment of PB‐1(6) with excess NaBH 4 reduces the twenty‐four imine bonds to amines yielding the reduced porphyrin box, rPB‐1(6), as shown in Scheme .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These unique synthetic hosts with well-defined cavities are capable of offering diverse weak interactions to recognize and encapsulate organic substrates 46 , constrain their orientations 47 , stabilize intermediates 48 , and mediate reaction kinetics, and thus used for their diverse applications 49 . Although the enzyme-like catalytic activities have been revealed for such special hosts by grafting/post-trapping catalytically active sites on cage skeletons or in cavities, respectively 25,44,45,[50][51][52] , visible light photocatalytic molecular cages toward organic reactions have been still very rarely realized because of the low quantum yield of excited states attributed to the cage-induced self-quenching effect 23,[53][54][55] . It has been envisioned that the ultrafast photo-induced energy/electron communication between hosts and cavity-confined guests in a close distance 23 may facilitate the rapid conversion of reaction reagents.…”
mentioning
confidence: 99%
“…The oxygen reduction reaction (ORR) is a central chemical transformation for biological and chemical energy conversion and storage, and can proceed through either a 2 e pathway to produce H 2 O 2 or a 4 e pathway to produce H 2 O. [1] Using electricity offers the possibility to drive this process with sustainable energy input, and in the context of molecular catalysts, structural and functional mimics of cytochrome c oxidase enzymes that perform ORR in biology have focused on the selective formation of H 2 O to better understand multielectron small molecule activation and develop efficient fuel cells. [2] Alternatively, H 2 O 2 is a valuable oxidant, energy carrier, and commodity chemical, and using electricity for H 2 O 2 production presents an environmentally green alternative to the traditional anthraquinone process for its synthesis, [3] with the key challenge to avoid further reduction to more thermodynamically favored H 2 O product.…”
mentioning
confidence: 99%